Analysis of the specific structure of the fundamental component of vocal sounds from the point of view of intonation evaluation - HARAJDA, Helena (Archives of Acoustics, 1983)
Finding it necessary to develop the acoustic basis for the evaluation of the correctness of vocal sound intonation, with consideration given to the clarity of intonation, the correctness of pitch attack and pitch stabilization, investigations were performed on the formation in the process of intonation of an isolated sound, of parameters of the fundamental component which provide information about the deep structure of this sound. The method of intonographic plotting was used and statistical calculations performed. The following quantities were considered: the duration of an isolated sound over one breath (t), the formation time of the amplitude and frequency of the fundamental component of an isolated, freely intoned sound (τA, τF), the value and variation of the amplitude level (A and ΔA), the fidelity of standard frequency reproduction and frequency variation (σ, v) within the limits of the quasi-steady state of sound. The investigations were performed on three groups of children and one of adolescents (20 voices in all).The results obtained have led to the conclusion that there are distinct differences in the deep structure of the fundamental component of isolated sounds intoned by the different age groups. These differences can constitute a physical basis for evaluating the ability to intone vocal sounds.